2010
DOI: 10.1029/2010pa001962
|View full text |Cite
|
Sign up to set email alerts
|

South Atlantic intermediate water mass geometry for the last glacial maximum from foraminiferal Cd/Ca

Abstract: [1] Paleoceanographic studies using benthic foraminiferal Cd as a nutrient tracer have provided a robust means of reconstructing glacial Atlantic Ocean water mass geometry, but a paucity of data from the South Atlantic above 1200 m has limited investigation of Antarctic Intermediate Water (AAIW) configuration and formation. A new Cd depth profile from Brazil margin sediments suggests that AAIW penetrated northward at 1100 m to at least 27°S in the glacial Atlantic. It exhibited substantially reduced d 13 C as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0
6

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 41 publications
4
22
0
6
Order By: Relevance
“…The western Atlantic glacial δ 13 C section includes published benthic data compiled previously (Curry & Oppo, ), data published since then (Burckel et al, ; Freeman et al, ; Hodell et al, , ; Hoffman & Lund, ; Keigwin & Swift, ; Lund et al, ; Lynch‐Stieglitz et al, ; Oppo et al, ; Poggemann et al, ; Praetorius et al, ; Rickaby & Elderfield, ; Tessin & Lund, ; Thornalley et al, ; Voigt et al, ), and our new data from the eight cores on the Demerara Rise, ranging in water depth from 376 to 2,642 m (Table and supporting information tables). The Western Atlantic CdW section includes data compiled previously (Marchitto & Broecker, ), data published since then (Makou et al, ; Poggemann et al, ), and new data from the Demerara Rise and Blake Outer Ridge. Revised distribution coefficients, discussed below, were applied to all published and new Cd/Ca data (supporting information tables).…”
Section: Methodsmentioning
confidence: 99%
“…The western Atlantic glacial δ 13 C section includes published benthic data compiled previously (Curry & Oppo, ), data published since then (Burckel et al, ; Freeman et al, ; Hodell et al, , ; Hoffman & Lund, ; Keigwin & Swift, ; Lund et al, ; Lynch‐Stieglitz et al, ; Oppo et al, ; Poggemann et al, ; Praetorius et al, ; Rickaby & Elderfield, ; Tessin & Lund, ; Thornalley et al, ; Voigt et al, ), and our new data from the eight cores on the Demerara Rise, ranging in water depth from 376 to 2,642 m (Table and supporting information tables). The Western Atlantic CdW section includes data compiled previously (Marchitto & Broecker, ), data published since then (Makou et al, ; Poggemann et al, ), and new data from the Demerara Rise and Blake Outer Ridge. Revised distribution coefficients, discussed below, were applied to all published and new Cd/Ca data (supporting information tables).…”
Section: Methodsmentioning
confidence: 99%
“…Additional observations include 3 δ 13 C c observations from the Demerara Rise (D.W. Oppo and W.B. Curry, personal communication, 2014), 15 paired δ 13 C c and Cd/Ca measurements [ Makou et al , ], and all reported δ 13 C c values from Marchitto and Broecker [] that were not present in other compilations. In total, the model is constrained with 241 δ 13 C c , 87 Cd/Ca, and 174 δ 18 O c observations (Figure ).…”
Section: Lgm Water Mass Decompositionmentioning
confidence: 99%
“…The modeled LGM 13 C as values do not give such a clear picture. AABW has a 13 C as value lower than −0.5‰, but AAIW is slightly positive in accord with previous works [Oppo and Horowitz, 2000;Makou et al, 2010]. GNAW is reconstructed to have 13 C as of 0‰-0.2‰, which is a less distinct signal than the 0.5‰ inferred by Marchitto and Broecker [2006].…”
Section: Air-sea Signature Of 13 Cmentioning
confidence: 99%
“…We might expect that sea ice expansion in the Southern Ocean could influence the production of mode and intermediate waters by altering surface budgets of heat and freshwater [Naveira Garabato et al, 2009] and modifying their preformed characteristics [Makou et al, 2010]. Changes in northward advection of intermediate waters in turn could impact silicic acid leakage.…”
Section: 1002/2013pa002588mentioning
confidence: 99%